Antidepressant-like effect of milk-derived lactoferrin in the repeated forced-swim stress mouse model - TAKEUCHI, Takashi (J Vet Med Sci, 2017)
We investigated the antidepressant-like effect of lactoferrin (Lf) in a repeated forced-swim test (FST) stress mouse model. FST was performed on days 1, 2, 7 and 14. Bovine Lf (bLf) or bovine serum albumin (BSA) was supplemented at 1% to the commercial diet after the first FST throughout the experimental period. The FST-control and FST+BSA group showed a marked increase in immobility time on day 2, which remained increased up to the 14th day, while the FST+bLf group showed a significant lower immobility time. Brain-derived neurotrophic factor (BDNF) content in the hippocampus significantly decreased in all of FST treated groups. These results suggest that bLf may improve the depressive-like symptoms induced by repeated FST.